Linguistic Theory and the Biblical Text - Ross, William A.; Robar, Elizabeth (Semitic Languages and Cultures, 2023)
This volume is the result of the 2021 session of the Linguistics and the Biblical Text research group of the Institute for Biblical Research, which addresses the history, relevance, and prospects of broad theoretical linguistic frameworks in the field of biblical studies. Cognitive Linguistics, Functional Grammar, generative linguistics, historical linguistics, complexity theory, and computational analysis are each allotted a chapter, outlining the key theoretical commitments of each approach, their major concepts and/or methods, and their important contributions to contemporary study of the biblical text. As academic disciplines and academic publishing proliferate and become more complex in a digital and global context, synthesising volumes such as this one have taken on new importance for both specialists and generalists alike. That is particularly the case in interdisciplinary areas of research. This volume therefore sets out to make linguistic theory clearer and more accessible to biblical scholars in particular, not only by careful explanation but also by specific illustration, drawing upon ancient Hebrew, Aramaic, and Greek languages within the Christian biblical corpus. The volume assists the reader in distinguishing the separate assumptions and scope of study for the separate theories, recognising methods of approach that can be applied to any of the theories, and the role of an umbrella theory to enable all the others to fruitfully interact. The bibliographies provided are structured for the non-specialist, noting handbooks, companions, and glossaries, general introductions, and foundational texts. In so doing, this volume presents not only a fully up-to-date cross-section of linguistic research in biblical scholarship but also an explicit path into the field, while highlighting important avenues for continued investigation and collaboration.